1998
DOI: 10.1073/pnas.95.7.3425
|View full text |Cite
|
Sign up to set email alerts
|

The transmembrane domain in viral fusion: Essential role for a conserved glycine residue in vesicular stomatitis virus G protein

Abstract: The transmembrane (TM) domains of viral fusion proteins are required for fusion, but their precise role is unknown. G protein, the fusion protein of vesicular stomatitis virus, was previously shown to lose syncytia-forming ability if six residues (GLIIGL) were deleted from its TM domain. The 20-residue TM domain of wild-type (TM20) G protein was thus changed into a TM domain of 14 residues (TM14). To assess possible sequence specificity for this loss of function, the two Gly residues in TM20 were replaced with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
150
4
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(171 citation statements)
references
References 63 publications
12
150
4
1
Order By: Relevance
“…The generality of these findings to other fusion proteins was suggested (Cleverley and Lenard, 1998). The HA of the A/Japan/305/57 strain used in the present study has two glycines within its TM domain; the one at position 530 is conserved among strains of influenza, whereas the glycine at position 520 (Figure 1) is a serine in most other strains.…”
Section: A Point Mutation In the Tm Domain Of Ha Inhibits Fusionsupporting
confidence: 72%
See 1 more Smart Citation
“…The generality of these findings to other fusion proteins was suggested (Cleverley and Lenard, 1998). The HA of the A/Japan/305/57 strain used in the present study has two glycines within its TM domain; the one at position 530 is conserved among strains of influenza, whereas the glycine at position 520 (Figure 1) is a serine in most other strains.…”
Section: A Point Mutation In the Tm Domain Of Ha Inhibits Fusionsupporting
confidence: 72%
“…It had been shown that mutation of either one of the two glycines within the TM domain of the G protein of VSV attenuates the extent of fusion, whereas mutation of both glycines inhibits full fusion but supports hemifusion (Cleverley and Lenard, 1998). The generality of these findings to other fusion proteins was suggested (Cleverley and Lenard, 1998).…”
Section: A Point Mutation In the Tm Domain Of Ha Inhibits Fusionmentioning
confidence: 99%
“…First, the transmembrane domain is absent in the structures. However, it is known that it plays an important role at the late stages of the fusion process as mutations of transmembrane glycin residues block fusion at a hemifusion stage [78]. Second, the structures of intermediate conformations of G, how they cooperate and how they interact with and deform the viral and target membranes are still very elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has also been shown that not only the ectodomain segment but also the membrane anchoring domain is required for VSV fusion activity (52,53).…”
Section: Determination Of the Rhabdovirus Fusion Peptidementioning
confidence: 99%